Biogeography and host-specificity of cyanobacterial symbionts in colonial ascidians of the genus Lissoclinum. Issue 5 (3rd July 2020) - Lopez-Guzman, Mirielle; Erwin, Patrick M.; Hirose, Euichi; López-Legentil, Susanna
Abstract : Ascidians are known to harbour bacterial symbionts in their tunics. In particular, the ascidian genus Lissoclinum can host abundant and diverse cyanobacterial associates. Here, we determined the diversity and host-specificity of cyanobacteria inhabiting 28 ascidian samples corresponding to eight Lissoclinum species: L. bistratum, L. midui, L. patella, L. punctatum, and L. timorense from Japan, L. aff . fragile and L. verrilli from the Bahamas, and L. perforatum from Spain and Chile. Cyanobacterial symbionts were characterized using both partial 16S rRNA gene sequences and sequences obtained for the entire 16S-23S rRNA internal transcribed spacer region (ITS). We found that both host species and geographic location played a role in structuring ascidian-cyanobacterial symbioses. Broad biogeographic trends included the dominance of Prochloron symbionts in Japanese ascidians and the presence of a novel cyanobacterial lineage in L. aff. fragile hosts from the Bahamas. Within each geographic region, a high degree of host-specificity was observed, where similar symbionts were recovered from ascidian hosts across multiple collection locations. Further, our analysis revealed the existence of nine distinct Prochloron clades in Japan, some of which corresponded to particular host species and sampling sites. For L. aff. fragile, further differences were observed between cyanobacterial symbionts in ascidians from reef and mangrove habitats. Our results showed high host-specificity in ascidian-cyanobacterial symbioses characterized by cryptic diversity and structured by host identity, location and habitat.